AB0698 MID-Term Effects of Rituximab in Connective Tissue Disorders Related Interstitial Lung Disease (ILD). (9th June 2015) - Lepri, G.; Avouac, J.; Airò, P.; Anguita Santos, F.; Bellando Randone, S.; Blagojevic, J.; Distler, O.; Garcìa Hernàndez, F.J.; Gonzalez Nieto, J.A.; Guiducci, S.; Jordan, S.; Limaye, V.; et al.
Abstract : Background: The treatment of ILD remains a challenge for the rheumatologist. Recent studies suggested a potential short-term benefit of rituximab (RTX) on connective tissue diseases developing ILD. Objectives: To compare RTX effects on ILD in patients with systemic sclerosis (SSc), mixed connective tissue disorder (MCTD) and anti-synthetase (SYN). Methods: Multicentre retrospective assessment of the effects of RTX on ILD comparing three patient populations: SSc (n=23), MCTD (n=6) and SYN (n=15). All underwent high-resolution computed tomography (HRCT) at baseline and lung function tests (LFTs) at baseline and at 1 and 2 years of follow-up. The primary outcomes were the mean change in predicted forced vital capacity (FVC) value and the percentage of responders defined by an increase in FVC of 10% or greater. Results: In SYN patients, although the change of FVC from baseline to 2 years was not statistically significant, a trend of improvement was observed (table 1 ). In SSc, discrepancies were observed with a trend of improvement at 1 year but a decline at 2 years. In MCTD, FVC remained table at 1 and 2 years of follow-up. In SYN patients, the percentage of responders for FVC was greater than in SSc (33.3% vs 9.5%) (p=0.1) and than in MCTD patients (33.3% vs 16.7%) (p=0.15). At baseline, SSc and MCTD patients had a higher FVC when compared to SYN population (table 1 ) and this finding may partially explain the major percentage of responders in SYN than in SSc. The percentage of responders in DLCO (gain ≥15%) was similar in SYN and SSc populations (27.3% and 23.8% respectively). Some patients received DMARDs and/or immunosuppressive treatment previously or/and concurrently to RTX; although this did not influence our findings, these treatments may influence the effects of RTX. RTX showed a satisfactory safety profile. Conclusions: Our data obtained in routine care provide for the first time outcomes in LFTs after 2 years of follow-up. The main results show a good safety profile supporting future development. We also observed a promising trend of improvement in the SYN group and indicate that the drug may provide a stabilization of the involvement of the lung in SSc and MCTD. Future trials on homogenous groups of patients are warranted to determine how rituximab may be positioned in the treatment of CTD-ILD, but the SYN group should be prioritized. Acknowledgements: EULAR scintific travel bursary Disclosure of Interest: G. Lepri: None declared, J. Avouac: None declared, P. Airò: None declared, F. Anguita Santos: None declared, S. Bellando Randone: None declared, J. Blagojevic: None declared, O. Distler Grant/research support from: received research funding from, 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation., F. J. Garcìa Hernàndez: None declared, J. A. Gonzalez Nieto: None declared, S. Guiducci: None declared, S. Jordan: None declared, V. Limaye: None declared, B. Maurer: None declared, V. Riccieri: None declared, A. Selva-O'Calaghan: None declared, M. Matucci Cerinic: None declared, Y. Allanore Grant/research support from: received research funding in relationship with the treatment of systemic sclerosis from Actelion, Bayer, Biogen Idec, BMS, Genentech/Roche, Inventive, Medac, Pfizer, Sanofi/Genzyme, Servier and UCB